Analysing Idiomatic Expressions in Coldplay's Album “A Head Full of Dreams”: A Linguistic Perspective - Diyo, Muhammad Panji; Faisal, Faisal (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This analysis highlights the significance of understanding idiomatic language in music as a means of appreciating the complexity of human expression and creativity. This study investigates the idiomatic expressions found in Coldplay's album "A Head Full of Dreams" through a linguistic lens. By conducting an analysis of selected tracks, specifically "A Head Full of Dreams," "Hymn for the Weekend," "Amazing Day," and "Birds," the research seeks to identify diverse categories of idioms and their interpretations within the context of the lyrics. Utilizing qualitative descriptive methodologies, the study examines how these idiomatic expressions enhance themes of hope, transformation, and emotional resonance within the music. The results indicate that idioms significantly enrich the lyrical content, offering cultural subtleties and amplifying the overarching messages conveyed in the songs. This analysis underscores the importance of comprehending idiomatic language in music as a means to appreciate the intricacies of human expression and creativity.